Innovative Digital Media for Elementary Education: Improving Critical Thinking and Learning Motivation - Chicha Anjelia Pratiwi; Cindy Merta Adelia; Cindy Rakhmah Mahardianti; Eka Putri Wulandari; Elvima Putri Nur Cahyani; Fiqri Irvandani; Erlin Ladyawati; Ika Suci Rahayu (EDUJAVARE: International Journal of Educational Research, 2026)
The rapid advancement of digital technology in the 21st century has significantly transformed educational systems worldwide, including elementary education in Indonesia. This study aims to improve students’ critical thinking skills and learning motivation through the implementation of innovative digital media in elementary education at SDN Kertajaya Surabaya. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model consisting of planning, action, observation, and reflection stages conducted in two cycles. The participants involved 30 elementary students. Data were collected through classroom observation, interviews, questionnaires, documentation, and critical thinking tests. The findings revealed that the implementation of innovative digital media such as educational videos, Canva-based materials, Quizizz, and interactive multimedia presentations significantly improved students’ classroom participation, critical thinking skills, and learning motivation. Students became more active in discussions, more confident in expressing opinions, and more capable of analyzing and solving contextual problems. Learning motivation also increased as students demonstrated greater enthusiasm, attention, and engagement during classroom activities. The study concludes that innovative digital media create interactive and student-centered learning environments that effectively support critical thinking development and learning motivation in elementary education during the digital era.